Clinical Significance of ABCG2 Haplotype-tagging Single Nucleotide Polymorphisms in Patients With Unresectable Non–Small Cell Lung Cancer Treated With First-line Platinum-based Chemotherapy. (June 2015) - Kim, Seok-Hyun; Kim, Moon Jin; Cho, Yu Ji; Jeong, Yi Yeong; Kim, Ho-Cheol; Lee, Jong Duk; Hwang, Young Sil; Kim, In-Suk; Lee, Suee; Oh, Sung Yong; Ling, Hui; Lee, Gyeong-Won
Abstract : Objectives: The ATP-binding cassette (ABC) ABCG2, involved in multidrug resistance (MDR) in cancer cells, plays an integral role in drug resistance. Single nucleotide polymorphisms (SNPs) have been identified in many MDR-associated ABC genes that seem to influence drug sensitivity/resistance through various mechanisms. Therefore, we investigated whether ABCG2 haplotype-tagging SNPs (htSNPs) were associated with clinical outcomes in patients with unresectable non–small cell lung cancer (NSCLC) treated with front-line platinum-based chemotherapy. Patients and Methods: We genotyped 4 ABCG2 htSNPs for 129 unresectable NSCLC cases treated with first-line platinum-based chemotherapy. Clinical characteristics, treatment outcomes, and predictive value of the htSNPs in patient response, survival, and adverse events related to platinum-based chemotherapy were analyzed according to each ABCG2 htSNP using the χ 2 test, Kaplan-Meier method, and Cox proportional hazard model. Results: The rs2725264 was significantly related to overall survival (OS) ( P =0.018, log-rank test). The median survival duration (in months) for patients with the rs2725264 T/T, T/C, and C/C genotypes was 35.75 (95% confidence interval [CI], 24.25-47.25), 34.25 (hazard ratio [HR] 1.27 [0.68 to 2.35]; 95% CI, 27.16-41.34), and 14.89 (HR 3.22 [1.26 to 8.24], 95% CI, 13.86-15.92), respectively. The rs2725264 was identified as an independent factor by Cox proportional hazard model analysis ( P =0.028). In the taxane-based groups, OS was associated with rs2725264 ( P =0.041), whereas in the gemcitabine-based groups, OS was associated with rs4148149 ( P =0.014). Conclusions: Our data suggest ABCG2 htSNPs rs2725264 (overall group and taxane-platinum combination group) and rs4148149 (gemcitabine-platinum combination group) were associated with OS in unresectable NSCLC patients treated with first-line platinum-based chemotherapy. Thus, the ABCG2 htSNP rs2725264 may be independently associated with OS in unresectable NSCLC patients treated with first-line platinum-based chemotherapy.